171k views
0 votes
Solve the following exponential equation. Express the solution set in terms of natural logarithms or common logarithms.​ Then, use a calculator to obtain a decimal approximation for the solution.

e^2x−4e^x+3=0

User Astrada
by
5.5k points

1 Answer

4 votes
x = 1.0986
x = 0

To solve this, solve it as if it was a quadratic equation by factoring. You should get the two numbers of -3 and -1.

Then, set e^x - 3 = 0
and e^x - 1 = 0

Solve that, then to get rid of e, ln or natural log both sides to get your final answers.

Hope this helps!
User Pztrick
by
5.1k points